Role of Pesantren in Da'wah and Media Literacy: Mitigating COVID-19 Challenges in Lamongan - Rahma, Zakiya (Jurnal Dakwah, 2023)
This study aims to explore the process of media literacy in the Karangasem Islamic Boarding School and Al-Ishlah Islamic Boarding School in Lamongan Regency, East Java, as an effort to mitigate the spread of Covid-19. In the context of the pandemic, pesantren plays an important role in increasing the awareness of students and the public about health protocols through the development of media literacy. The research method used is a qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation. The results of the study show that the two Islamic boarding schools have implemented an effective media literacy program, in which the Karangasem Islamic Boarding School through the INFOKOM program and the Al-Ishlah Islamic Boarding School with their journalistic activities, have succeeded in equipping students with critical skills in accessing and evaluating information. This study concludes that media literacy in Islamic boarding schools not only contributes to improving students' understanding of Covid-19, but also serves as a means to disseminate accurate information to the public, thus playing a role in mitigating the spread of the virus. This finding is expected to be a model for other Islamic boarding schools in developing media literacy in the digital era, especially in the context of public health.